Organization and identity - Linstead, Alison, 1971-; Linstead, Stephen, 1952- (London ; New York : Routledge, 2005)
The contributors to the collection bring approaches from current philosophising into the area of organization theory and critically assess their relevance and impact.
Half-Title; Series Title; Title; Copyright; Contents; Contributors; Acknowledgments; 1 Introduction; 2 Now where was I?; 3 Theorizing narrative identity; 4 Self and other in everyday existence; 5 Living a story and storying a life; 6 Career as a project of the self and labour process discipline; 7 Fetish failures; 8 The mission statement as epideictic rhetoric; 9 Other work; 10 Beyond happy families; 11 Casting the other to the ends of the Earth; 12 Making global subjects; 13 Fluid identities and ungendering the future; 14 Identity aesthetics; Author index; Subject index.
Includes bibliographical references and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Identity (Psychology) -- Social aspects; Identité (Psychologie) -- Aspect social; PSYCHOLOGY -- Social Psychology; Identity (Psychology) -- Social aspects